IMPLEMENTASI KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA DI KOTA SEMARANG - Mirtha Ega Priandari; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
The regulation of street vendors is one of the local government’s efforts to maintain order in public spaces while supporting the economic sustainability of the informal sector. The city of Semarang regulates street vendors through Semarang City Regulation No. 3 of 2018. However, in practice, the implementation of this policy still faces various challenges, such as high rates of violations, limited resources, and low levels of vendor compliance with existing regulations. This study aims to analyze the implementation of the street vendor management policy in the City of Semarang and to identify the supporting and hindering factors in its implementation. This study employs a qualitative approach with a descriptive research design. Data collection techniques include interviews, observations, and documentation, involving informants from the Trade Department, the Civil Service Police Unit, the Spatial Planning Department, subdistricts, villages, and street vendors. The research analysis utilized George Edward III’s policy implementation theory, which encompasses communication, resources, disposition, and bureaucratic structure. The results indicate that the implementation of the street vendor management policy in Semarang City has not yet been optimal. This is attributed to limitations in human resources and budget, ineffective policy communication and outreach, as well as insufficient inter-agency coordination. In addition, low awareness and compliance among vendors with existing regulations also pose obstacles to policy implementation. Therefore, it is necessary to strengthen interagency coordination, increase outreach to vendors, and enhance oversight and enforcement of regulations so that the implementation of policies regarding street vendor management can proceed more effectively